Design and development of Android app to promote Singapore's hawker food culture and appreciation : hawk and chope - Seah, Pearlyn Hui Qin (2019)
This report summarises the process of developing an Android application using Ionic Framework and Firebase as the database. My project particularly aims to design and develop and application for foreigners to better appreciate Singapore’s hawker culture. The report starts off with a background research and the objectives of the application. Future in, an analysis of Ionic and Firebase is shared along with the project planning and application development process. Towards the end, I share a report on the testings done. Lastly, I concluded the report by sharing the challenges faced and potential future improvements.